(untitled) (Superficies y Vacío, 2021)
Amber is a fossilized natural resin found in specific areas of the world; its geographical origin is associated to a characteristic color. Amber all over the world share basic characteristics due to a common polymeric matrix; however, its color is associated to the environment where it was formed. In this work, based on a compositional analysis, it is proposed that yellow color of Mexican amber is originated from the sulfur physical and chemical interaction within its polymeric matrix. The effect of sulfur present in yellow Mexican amber is studied by employing X-ray photoelectron and UV-Vis spectroscopies. Results show that sulfur is incorporated inside the polymer matrix with two different chemical environments; one related with sulfur-carbon bonds and the other with sulfur-sulfur bonds. The optical transmission spectrum simulated considering amber as a composite material reproduce the scattering contribution observed experimentally.